Humanitarian intelligence a practitioner's guide to crisis analysis and project design - Zwitter, Andrej (Security and professional intelligence education series., 2016)
Humanitarian intelligence refers to the use of investigative and analytical techniques in service of rapid and continuous assessment, project and program development, impact evaluation, and learning. It focuses just as much on how to use early warning indicators to assess risks, evaluate trends, and write early warning analyses as it does provide guidance on the operational design of humanitarian relief efforts.